Patient safety culture in private hospitals in China: a cross-sectional study using the revised Hospital Survey on Patient Safety Culture - Liu, Yan; Xu, Jianing; Yang, Xiaoguang; Yue, Liu; Li, Guohong; Mah, Alastair P. (Frontiers in Public Health, 2024)
Background This study aimed to translate the revised Hospital Survey on Patient Safety Culture (HSOPSC 2.0) to Mandarin, evaluate its psychometric properties, and apply it to a group of private hospitals in China to identify the determinants associated with patient safety culture. Methods A two-phase study was conducted to translate and evaluate the HSOPSC 2.0. A cross-cultural adaptation of the HSOPSC 2.0 was performed in Mandarin and applied in a cross-sectional study in China. This study was conducted among 3,062 respondents from nine private hospitals and 11 clinics across six cities in China. The HSOPSC 2.0 was used to assess patient safety culture. Primary outcomes were measured by the overall patient safety grade and patient safety events reported. Results Confirmatory factor analysis results and internal consistency reliability were acceptable for the translated HOSPSC 2.0. The dimension with the highest positive response was “Organizational learning - Continuous improvement” (89%), and the lowest was “Reporting patient safety event” (51%). Nurses and long working time in the hospital were associated with lower assessments of overall patient safety grades. Respondents who had direct contact with patients, had long working times in the hospital, and had long working hours per week reported more patient safety events. A higher level of patient safety culture implies an increased probability of a high overall patient safety grade and the number of patient safety events reported. Conclusion The Chinese version of HSOPSC 2.0 is a reliable instrument for measuring patient safety culture in private hospitals in China. Organizational culture is the foundation of patient safety and can promote the development of a positive safety culture in private hospitals in China.